Constructing professional identities in new figured worlds: Foreign language teachers transitioning to English teaching in Vietnam. Issue 1 (1st January 2023) - Tran, Hao; Taylor-Leech, Kerry
ABSTRACT: Teachers stand at the face of educational change, and it is therefore important to understand the identity work that they do if reform is to be successful. This paper explores how two Vietnamese university language teachers renegotiated their professional identity in the context of dramatic changes to language provision in the tertiary-sector in Vietnam. These changes were brought about by higher education reforms and the national plan to improve the quality of English language teaching, commonly referred to as National Project 2020. The authors use the concept of Figured Worlds, and the related notions of figurative and positional identities, to analyse the narratives that permeated these teachers' professional identities. Their storylines provide an illustrative case which highlights the complex forces that reshape teacher professional identities in times of externally imposed reform and professional transition. The findings of our study show that prior experience, language affiliation, emotional responses to change, professional orientations and actions, confidence, and self-esteem were key influential forces shaping the teachers' identities. The findings have relevance for the broad field of teacher professional identity as well as for language education in Vietnam and other Southeast Asian countries.